Multiple-Band Terahertz Metamaterial Absorber Using Multiple Separated Sections of Metallic Rectangular Patch - Wang, Ben-Xin; He, Yuanhao; Lou, Pengcheng; Xu, Nianxi; Wang, Xiaoyi; Wang, Yanchao; Cao, Jianjun (Frontiers in Physics, 2020)
Multiple-band metamaterial absorbers have been widely reported using the co-planar or layered design methods. However, these obtained absorption devices are of complex structure, large unit size, heavy weight and time-consuming construction steps. Herein, an alternative design strategy is suggested to realize the multiple-band absorption at terahertz frequency. By introducing air gaps into the rectangular metallic patch, the original rectangular resonator can be divided into multiple sub-structures (or separated sections), and the combined effect of the localized resonance response of these sub-structures (or separated sections) gives rise to the multiple-band absorption. More importantly, the size, position and number of air gaps play the important roles in controlling the resonance performance of the absorption peaks and even in regulating the amount of the absorption peaks. Compared with the existing multiple-band absorption design strategies, the proposed approach does not increase the unit size, nor need to stack multiple layers, which provides important guidance for the design of multiple-band terahertz metamaterial absorbers with simple, compact and easy to fabricate. for full details.